Medieval Multilingualism in Poland: Creating a Corpus of Greater Poland Court Oaths (Rotha) - Kopaczyk, Joanna; Włodarczyk, Matylda; Adamczyk, Elżbieta (Studia Anglica Posnaniensia, 2016)
In this paper we introduce the research plan for the preparation of a searchable electronic repository of the earliest extant legal oaths from medieval Poland drawing on the expertise in historical corpus-building developed for the history of English. The oaths survive in the overwhelmingly Latin land books from the period between 1386 and 1446 for six localities Greater Poland, in which the land courts operated: Poznań, Kościan, Pyzdry, Gniezno, Konin and Kalisz. A diplomatic edition of the oaths was published in five volumes by Polish historical linguists (Kowalewicz & Kuraszkiewicz 1959–1966). The edition is the only comprehensive resource of considerable scope (over 6300 oaths from the years 1386–1446) for the study of the earliest attestations of the Polish language beyond glosses. Recognising some limitations, but most of all its unparalleled coverage of the coexistence of Latin and the vernacular, the ROThA project embarks on transforming the edition into an open up-to-date digital resource. We thus aim to facilitate research into the history of Polish and Latin as well as of the legal system and the related social and linguistic issues of the period.